IMPROVING THE DEVELOPMENT OF SMALLHOLDER COCOA PLANTATIONS IN PADANG PARIAMAN DISTRICT - Chandra Refolta (Journal of Socio-Economics on Tropical Agriculture (Jurnal Sosial Ekonomi Pertanian Tropis) (JOSETA))
Padang Pariaman is one of three regions in West Sumatra designated as a Cocoa Commodity Agricultural Development Area, along with Pasaman Regency and West Pasaman Regency (Kementan RI, 2018). As stated in the Strategic Plan of the Padang Pariaman Regency Agriculture and Food Security Service for 2021-2026, cocoa is one of the leading commodities in the plantation subsector which is a mainstay for Padang Pariaman Regency as a driver of the community's economy. Data from the last few years shows that the area of smallholder cocoa plantations in Padang Pariaman Regency continues to decline (BPS Padang Pariaman, 2024). The decline in cocoa area and production in Padang Pariaman Regency was caused by the lack of management of cocoa plantations by farmers, resulting in attacks by Plant Pest Organisms (OPT) on cocoa plants, one of which was the Phytophthora palmivora fungus (Nasir, 2016). Policy recommendations that can be implemented by the Department of Agriculture and Food Security of Padang Pariaman Regency in an effort to increase the development of smallholder cocoa plantations include; 1).  Determine a direction map for increasing the development of smallholder cocoa plantations in Padang Pariaman Regency based on land suitability classes for cocoa plants, and 2). Establish policy guidelines for the use of certified superior seeds for the rehabilitation and rejuvenation of people's cocoa plantations in Padang Pariaman Regency.